Reform of the international economic order: Uncertainty and economic policy coordination. (October 2022) - Ding, Haoyuan; Jin, Yuying; Koedijk, Kees; Ma, Chang
Abstract: This special issue contains a selection of articles on globalization and fintech. The contributions provide new insights on reform of the international economic order, paying special attention to uncertainty and economic policy coordination. They will certainly help improve our understanding of these topics.